30.4k views
4 votes
5x + 2(x - 3) = -2(x - 1)

User CeeTee
by
4.9k points

2 Answers

1 vote

Answer:

see explanation

Explanation:

Given

5x + 2(x - 3) = - 2(x - 1) ← distribute both sides

5x + 2x - 6 = - 2x + 2, that is

7x - 6 = - 2x + 2 ( add 2x to both sides )

9x - 6 = 2 ( add 6 from both sides )

9x = 8 ( divide both sides by 9 )

x =
(8)/(9\\)

User Williamsurles
by
5.4k points
4 votes

Answer:

x = 8/9

Explanation:


5x + 2(x-3) = -2(x-1)\\5x + 2(x) + 2(-3) = -2(x) - 2(-1)\\5x + 2x - 6 = -2x + 2\\9x = 8\\x = (8)/(9)

User Charles Holbrow
by
5.1k points